2022
DOI: 10.3390/molecules27238180
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants, Biosurfactants, and Non-Catalytic Proteins as Key Molecules to Enhance Enzymatic Hydrolysis of Lignocellulosic Biomass

Abstract: Lignocellulosic biomass (LCB) has remained a latent alternative resource to be the main substitute for oil and its derivatives in a biorefinery concept. However, its complex structure and the underdeveloped technologies for its large-scale processing keep it in a state of constant study trying to establish a consolidated process. In intensive processes, enzymes have been shown to be important molecules for the fractionation and conversion of LCB into biofuels and high-value-added molecules. However, operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…In whole cell biocatalysis, in addition to external environmental factors, the barrier functions of the cell wall and membrane affect the catalytic efficiency. 18 Therefore, we selected four surfactants to improve the production efficiency of NMN. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In whole cell biocatalysis, in addition to external environmental factors, the barrier functions of the cell wall and membrane affect the catalytic efficiency. 18 Therefore, we selected four surfactants to improve the production efficiency of NMN. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address this intricate structural obstacle, a variety of physical, physicochemical, and biological pretreatment methods have been used, significantly contributing to the conversion of lignocellulosic biomass [7]. However, some obstacles persist in the process of enzymatic hydrolysis of lignocellulosic biomass, including those related to nonproductive binding, limited total solid loading, and reduced enzyme activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…To address this intricate structural obstacle, a variety of physical, physicochemical, and biological pretreatment methods have been used, significantly contributing to the conversion of lignocellulosic biomass [7]. However, some obstacles persist in the process of enzymatic hydrolysis of lignocellulosic biomass, including those related to nonproductive binding, limited total solid loading, and reduced enzyme activity [7]. In order to maximize the effectiveness of the enzymatic hydrolysis of vegetal biomass, it has been suggested that surfactant molecules can lower surface tension and alter the structure of plant biomass and can be employed as effective additives [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations